METODE HIWAR SEBAGAI SALAH SATU CARA MENCEGAH ISLAMOPHOBIA - Abdusshomad, Alwazir (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
Islam is a perfect religion. A belief that there is no god but Allah, and Muhammad SAW is the messenger of Allah. Based on this belief, the following human must have the pillars of faith and the pillars of Islam. Currently, the understanding of Islam is far from what it should be. Most non-Muslims consider Islam a strict religion; some even say that the religion of terrorists is Islam. Ignorance about the religion of Islam makes non-Muslim communities in the West, in particular, afraid to establish communication with Muslims. Much news that corners the Islamic religion. The role of the mass media is essential in reporting. Therefore, this study discusses what Islamophobia is and how to overcome it. This research is library research. This research is expected to enlighten to reduce the existence of Islamophobia, especially in the West.